The Secularisation of Sin in the Nineteenth Century - Erdozain, Dominic (The journal of ecclesiastical history, 2011)
This article argues that the post-secularisation historiography of the past twenty years has erred in neglecting theological categories of analysis. Committed to challenging the explanatory power of the secularisation thesis, it has established a new paradigm of ‘survival’ and ‘redefinition’, interpreting the sub-Christian morality of the twentieth century as a robust continuation of the pervasive Christianity of the nineteenth. A more theological approach, however, demonstrates that much of the ‘success’ of Victorian religion was achieved at the cost of the soteriology that had fired the religious boom. Tracing a shift from an ‘internal’ concept of sin to an ‘external’ notion of vice, it is argued that Evangelicalism created its own mechanism of secularisation, distilled in the shift from Evangelicalism to temperance agitation.